KINERJA PEGAWAI PERUSAHAAN DAERAH AIR MINUM (PDAM) KABUPATEN BENGKAYANG - Yeni Marsela E.21109029 (PublikA, Jurnal Ilmu Administrasi Negara, 2013)
Water  services clean in Bengkayang still experiencing a variety of problems, including: less smooth distribution of water to customers, less maximal performance of employees in performing their duties, and the lack of facilities and infrastructure in the local water company Bengkayang. This study aims to determine how the employee's performance Regional Water Company (PDAM) Regency Bengkayang. This study used a descriptive research model with data processing techniques of qualitative analysis. In this study, the performance of employees include 5 things: productivity, quality of service, responsiveness, responsibility, and accountability. The results of the data analysis found that the ability of the Regional Water Company (PDAM) Bengkayang as water service providers must rapidly in response to, handle complaints / customer complaints and to make improvements to the installation, water quality and facilities on the ground support vehicles. The conclusion of this study is the success rate of the officer should be supported with good facilities, this will affect the results obtained but the performance PDAM Bengkayang, although the facilities are not adequate to complete the job properly. Key words: Performance, Behavior, and Quality of Service